Imagining the future : historically Black colleges and universities - a matter of survival - Crosby, Gary B.; White, Khalid A.; Chanay, Marcus A.; Hilton, Adriel A. (Contemporary perspectives on access, equity, and achievement., 2022)
"The Nation's Historically Black Colleges and Universities (HBCUs) are more culturally revered today than ever. As public health and socioeconomic inequity gaps continue to widen between the African American community and other racial groups, the HBCUs embody a shared support system. Since the 1800s, this body of prestigious higher education institutions have represented trusted pathways for the advancement of our community. With these historical accomplishments in mind, it is crucial for HBCUs and their leadership to create a vision for generations to come. Visionary leadership is a must for our storied institutions to advance beyond just surviving into fully thriving. As such, our book project, Imagining the Future: Historically Black Colleges and Universities - A Matter of Survival, offers cutting edge ideas, suggestions and advice from HBCU alumni, proponents, faculty leaders, and researchers for HBCU leadership to cultivate success today and into the foreseeable future. Imagining the Future: Historically Black Colleges and Universities - A Matter of Survival promises timely, relevant and emergent scholarship as well as perspectives for HBCU leadership, HBCU scholars and HBCU supporters"--